Information sources, perceived personal experience, and climate change beliefs - ROSENTHAL, Sonny (Institutional Knowledge at Singapore Management University, 2022)
This study proposes and tests a model of serial mediation based on the norm activation model and value-belief-norm theory. It argues that beliefs about climate change are related to perceived personal experience, which is related to the use of different information sources. Structural equation modeling of survey data from 1084 adult residents of Singapore found mixed support for three hypotheses. Results showed that perceived personal experience of climate change was related to the use of traditional media (β = 0.20), social media (β = 0.16), and interpersonal sources (β = 0.13), but not institutional sources. Perceived personal experience of climate change was positively related to agreement with the new ecological paradigm (β = 0.36), awareness of consequences (β = 0.26), ascription of responsibility (β = 0.25), and personal norm (β = 0.20). Generally, perceived personal experience of climate change mediated the relationship between traditional media, social media, and interpersonal sources and each type of climate change belief. This suggests some types of information, but not all, offer vicarious experiences of an environmental phenomenon that largely escapes direct perception. In addition to those theoretical implications, this work has practical implications for audience segmentation and climate change communication.